PENERAPAN PROBLEM BASED LEARNING DALAM UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS PADA PEMBELAJARAN LOGIKA MATEMATIKA - Lyna Yuni Artika (Tadzkirah : Jurnal Pendidikan Dasar, 2020)
Learning mathematics has become a necessity, given that mathematics always experiences development especially in the process of thinking following developments in the world of technology. Learning mathematics skillfully will be able to give birth to students who can be facilitated in their ability to think critically, creatively, systematically and logically. Critical thinking is the ability of a person to carry out activities in an organized manner to achieve deeper understanding in a more perfect direction. In facilitating students' critical thinking skills, problem-based learning can be used. Problem-based learning (Problem Based Learning) is a learning that makes the problem as the basis. PBL provides opportunities for students to develop their critical thinking skills. This research is an experimental study involving 2 banjit vocational high school students. In this research problem-based mathematics learning is applied in an effort to improve students' mathematical critical thinking skills on mathematical logic material. Based on the results of the analysis of the discussion data it was concluded that there was an increase in students' mathematical critical thinking skills from cycle I to cycle II.